Spirulina Platensis Residue (SPR) Pyrolysis: Temperature's Effect on Yield and Biochar Characteristics - Jamilatun, Siti; Pitoyo, Joko; Arifah, Zulia (Indonesian Journal of Chemical Engineering, 2023)
Biochar has potential as alternative solution to overcoming the problem of renewable energy needs, improving land structure for agriculture, and supplying industrial needs as absorbent material with high absorption. Biochar has a high carbon content that it obtains from the biomass pyrolysis process. In this experiment, the main material was biomass obtained from the Spirulina platensis residual (SPR). The temperature effect on the yield and characteristic of biochar from SPR were studied. The research was conducted in the fixed-bed reactor with 40 mm of inside diameter, 44 mm of outside diameter, and 600 mm of height. The reactor was supported with an electrical heater from a nickelin coiled along the outside surface of reactor. The experiments were carried out with temperatures ranging from 300 to 700ºC. Biochar analysis was performed by the Brunauer-Emmett-Teller (BET) method. Results indicated that the yield of biochar decreased with increasing temperature. Conversely, the surface area, the total volume of pore, and the radius of pore increase with an increase in temperature. The best temperature conditions to produce the biochar are 600ºC, with the product yield of 27.9 wt.%, surface area of ​​13.5 m2/gr, total pore volume of 0.041 cc/gr, and diameter of 2,688 nm.